PERBEDAAN ECONOMIC VALUE ADDED BERDASARKAN SIKLUS HIDUP PERUSAHAAN DAN PASAR - Harning Priyastuty; Bambang Subroto; Wuryan Andayani (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. This study aims to examime whether corporate and market life cycle situation have impact on financial performance. The situation that is experienced by company has impact on future financial performance. This matter is due to the risk that is taken by the company to confront that situation. The relationship between risk and return in this study will be explained by prospect theory. This study use the population of manufacture company listed in BEI period 2013-2015. This study use 115 sample of manufacture company. Those samples will be classified based on nine combination of corporate and market life cycle and will be tested with comparative test. The data analysis method of this study is mean rank comparative with kruskal wallis test. The result shows that corporate and market cycle have no impact on future financial performance. The result shows that there is no difference of financial performance based on corporate and market life cycle. This matter is caused by act of determine strategic risk that need a lot of another internal and external environment consideration